2005
DOI: 10.1097/01.ta.0000197279.97113.0e
|View full text |Cite
|
Sign up to set email alerts
|

Are Plain Radiographs of the Spine Necessary during Evaluation after Blunt Trauma? Accuracy of Screening Torso Computed Tomography in Thoracic/Lumbar Spine Fracture Diagnosis

Abstract: Admission CAP CT obtained as part of the routine trauma evaluation in these high-risk patients is more sensitive than plain radiographs for evaluation of the TL spine after blunt trauma. In addition, CAP CT can be performed faster. Omission of plain radiographs will expedite accurate evaluation allowing earlier treatment and mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 14 publications
0
51
0
Order By: Relevance
“…CT is superior to plain imaging for the detection of significant injury to the TL spine [15,16,[70][71][72]. Berry et al [73] quote 100% sensitivity and 97% specificity for CT to detect TL fracture compared to 73% sensitivity and 100% specificity for plain radiographs. Furthermore, radiographs are inherently compromised in the lateral projection due to the shoulders and hence the cervicothoracic junction region tends to be evaluated and cleared on the anteroposterior view alone.…”
Section: Clearing the Thoracolumbar Spinementioning
confidence: 99%
See 1 more Smart Citation
“…CT is superior to plain imaging for the detection of significant injury to the TL spine [15,16,[70][71][72]. Berry et al [73] quote 100% sensitivity and 97% specificity for CT to detect TL fracture compared to 73% sensitivity and 100% specificity for plain radiographs. Furthermore, radiographs are inherently compromised in the lateral projection due to the shoulders and hence the cervicothoracic junction region tends to be evaluated and cleared on the anteroposterior view alone.…”
Section: Clearing the Thoracolumbar Spinementioning
confidence: 99%
“…Where a CT of the chest/abdomen/pelvis (CT-CAP) has already been performed on admission then the use of reformats is superior to plain imaging [73]. In the rare circumstances where a CT-CAP has not been deemed necessary then we would argue that a CT of the entire spine should be performed.…”
Section: Clearing the Thoracolumbar Spinementioning
confidence: 99%
“…In our study, sensitivity of direct radiogram was 51%, therefore diagnosis of fracture could only be made with CT that was performed after direct radiograms were obtained in 49% of the patients. Regarding the sensitivity of X-ray radiography, previous studies have reported rates ranging from 33% to 74% [21][22][23][24] . The different ratios between reports may be due to the different number of patients and vertebral fractures between studies, and it may also be stem from using various types of CT scans in these studies.…”
Section: Wang Et Almentioning
confidence: 99%
“…In the light of the findings of our study, it is understood that transverse process or spinous process fractures compared the vertebral body fractures more easily detected by X-ray radiography. Berry et al 21 evaluated 26 patients with thoracolumbar spine fractures and found 73% sensitivity for X-ray radiography. In their study, they found 64% of the fracture was at the transverse process that this rate is significantly higher than ours, and this situation may lead to differences between studies.…”
Section: Wang Et Almentioning
confidence: 99%
“…In fracture-dislocation the degree of translation of vertebral body is also measured. Vertebral translation greater than 3.5 mm has been reported to be associated with The sensitivity of CT for depicting TL fractures ranges from 95-100% (26,27). It is also more accurate than magnetic resonance imaging (MRI) for detecting fractures involving the posterior elements, and for demonstration of the size and location of loose osseous fragments (27).…”
Section: Multidetector Computed Tomography (Mdct)mentioning
confidence: 99%